Received Pronunciation as a Model Pronunciation of the British English: Its History and Evolution - Arzu Karaeva Nizami qizi (Zien Journals, 2023)
This article studies the main features and the evolution of the Received Pronunciation, the standard pronunciation of British English, also known as the Queen’s English, the BBC English, etc. History and social status evolution of the RP are discussed as well as latest innovations in this variety of English pronunciation. This study aims to help English learners correct their pronunciation, making it sound more natural and modern, and reduce phonetic interference.
Keywords: Received Pronunciation; model pronunciation; accent; variety